The restoration and refunctionalisation of medieval fortified manor houses by the Portuguese dictatorial regime (1926–1974) - Santos, Joaquim Rodrigues dos (Acta historiae artis Slovenica, 2023)
In the Modern Age, most fortified manor houses in Portugal fell into ruin, due to the lack of dignified living conditions, the obsolescence of defensive structures, and the decline decay of aristocratic families. However, between 1933 and 1974, many ruined fortified manor houses were restored by the Portuguese dictatorial regime. The nationalist dictatorship of Estado Novo used heritage as an ideological instrument of propaganda. This proposal aims to analyse the context of the ideological restoration of medieval fortified manor houses by the dictatorial regime, addressing symbolisms, restoration actions, and the contextualisation of fortified manor houses in Portugal by focusing on particular case studies.
Keywords: architectural heritage; arhitekturna dediščina; diktatura Estado Novo; Estado Novo dictatorship; ideological propaganda; ideološka propaganda; Medieval castles; prenova; refunctionalization; renovation; restavriranje; sprememba namembnosti; srednjeveški gradovi